Reconciling human health with the environment while struggling against the covid-19 pandemic through improved face mask eco-design - YILAN, GÜLŞAH (My University, 2022)
© 2022. The Author(s).Surgical masks have become critical for protecting human health against the COVID-19 pandemic, even though their environmental burden is a matter of ongoing debate. This study aimed at shedding light on the environmental impacts of single-use (i.e., MD-Type I) versus reusable (i.e., MD-Type IIR) face masks via a comparative life cycle assessment with a cradle-to-grave system boundary. We adopted a two-level analysis using the ReCiPe (H) method, considering both midpoint and endpoint categories. The results showed that reusable face masks created fewer impacts for most midpoint categories. At the endpoint level, reusable face masks were superior to single-use masks, producing scores of 16.16 and 84.20 MPt, respectively. The main environmental impacts of single-use masks were linked to raw material consumption, energy requirements and waste disposal, while the use phase and raw material consumption made the most significant contribution for reusable type. However, our results showed that lower environmental impacts of reusable face masks strongly depend on the use phase since reusable face masks lost their superior performance when the hand wash scenario was tested. Improvement of mask eco-design emerged as another key factor such as using more sustainable raw materials and designing better waste disposal scenarios could significantly lower the environmental impacts.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisciplinary